# Solve for y -11/y=-22/(y-4)

-11y=-22y-4
Multiply the numerator of the first fraction by the denominator of the second fraction. Set this equal to the product of the denominator of the first fraction and the numerator of the second fraction.
(-11)⋅(y-4)=y⋅-22
Solve the equation for y.
Simplify (-11)⋅(y-4).
Apply the distributive property.
-11y-11⋅-4=y⋅-22
Multiply -11 by -4.
-11y+44=y⋅-22
-11y+44=y⋅-22
Move -22 to the left of y.
-11y+44=-22y
Move all terms containing y to the left side of the equation.
Add 22y to both sides of the equation.
-11y+44+22y=0
11y+44=0
11y+44=0
Subtract 44 from both sides of the equation.
11y=-44
Divide each term by 11 and simplify.
Divide each term in 11y=-44 by 11.
11y11=-4411
Cancel the common factor of 11.
Cancel the common factor.
11y11=-4411
Divide y by 1.
y=-4411
y=-4411
Divide -44 by 11.
y=-4
y=-4
y=-4
Solve for y -11/y=-22/(y-4)

## Our Professionals

### Lydia Fran

#### We are MathExperts

Solve all your Math Problems: https://elanyachtselection.com/

Scroll to top